Quality of adolescent and youth-friendly sexual and reproductive health services and associated factors in Ethiopia: a systematic review and meta-analysis - Getachew Assefa Zenebe; Temesgen Muche Ewunie; Moges Mareg Belay; Abinet Meno Abose (Frontiers Media S.A., 2023)
BackgroundLow-quality health care services are linked to a variety of health problems, which can have negative effects on adolescent and youth health. As a result, national data is crucial to providing high-quality healthcare to adolescents and youths in order to promote their health, wellness, and growth.ObjectiveTo examine the quality of young people's sexual and reproductive health care services and factors associated with service satisfaction in Ethiopia.MethodsThis review was carried out in accordance with the PRISMA guideline. We reviewed published data related to the quality of adolescent and youth-friendly sexual and reproductive health services (AYSRHS) in Ethiopia from January 02, 2002 to December 30, 2022. Relevant studies were identified through Google Scholar, PubMed, Cochrane Library, Science Direct, and HINARI. The extracted data was imported into STATA version 14.0 software for analysis. Heterogeneity among the reported prevalence of studies was checked using χ2 and I2 tests. The publication bias was examined by Egger's correlation and Begg's regression intercept tests at a 5% significance level.ResultsThe national pooled magnitude of structural, process, and output dimensions of quality of AYSRHS is 54.22% (95% CI: 33.21, 75.24%), 35.44% (95% CI: 24.95, 45.93%), and 57.01% (95% CI: 50.32, 63.7%), respectively. Being female (AOR: 1.61, 95% CI: 1.14-2.27), employed (AOR: 1.82, 95% CI: 1.06-3.14), waiting <30 min to get services (AOR: 2.7, 95% CI: 1.69-4.31), and getting information on the availability of services (AOR: 1.56, 95% CI: 1.15-2.11) were significantly associated with client satisfaction with AYSRHS.ConclusionThe overall magnitude of quality of AYSRHS in the three dimensions is far below WHO quality standards, which are 75 percent for good quality. Sex, employment status, waiting time to get services, and information on the availability of services were significantly associated with client satisfaction with AYSRHS. Therefore, different stakeholders on different levels should work together to strengthen the quality of AYSRHS concidering the above factors.Systematic review registrationIdentifier [CRD42023422667].